Develop and implementation of PC based controller for humanoid robot using digital potentiometer - Hairol Nizam Mohd Shah; Mohd Fairus Abdollah; Zalina Kamis; Mohd Shahrieel Mohd Aras; Mohd Rizuan Baharon; Muhammad Zakwan Akmal Sallehoddin (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper introduced to develop and implementation of PC based controller for humanoid robot using digital potentiometer. The main objective in this paper is to develop and implement the joystick controller by using a digital potentiometer circuit board that be able to control the humanoid robot movement. The Arduino board and digital potentiometer will be integrated by connecting both pins in between wiper, W pin and ground, GND to the DB9 pins of remote control platform, which is TX and RX pins respectively. Humanoid robot as known as TOMY i-SOBOT is used as a preferred model due to wide usage in many applications. A digital potentiometer will be transmitted the voltage and current value depend on the digital level through serial communication to give the instruction for humanoid robot movement. The humanoid movement based on Guided User Interface (GUI) where the user give a commands by pressing the button on the GUI such as turn left, right, forward, and reverse. The results show that the humanoid movement able to control based on the voltage and current in a digital potentiometers value.